Inhibiting effect of calcium ions on surface reconstruction for water electrolysis - Seow, Justin Zhu Yeow (2023)
Electrochemical generation of hydrogen can facilitate efficient large-scale energy storage for electricity produced from intermittent renewable energy sources such as solar energy and wind energy. While this process, also known as water electrolysis, uses water with supporting ions (such as acid or alkali) as the reactant electrolyte, ultrapure water is usually used to prepare the electrolyte. To reduce its strain on the scarce clean water resources, attempts have been made to directly use seawater to prepare the electrolyte. Although it has been well-known that chlorine evolution reaction (CER) competes with the already sluggish anodic oxygen evolution reaction (OER) in the presence of chloride ions (the most prominent anion in the seawater), Dionigi et al. has established that at pH > 7.5 and OER overpotential < 480 mV, anodic reactions occur with 100% OER selectivity. Nonetheless, various studies have reported inferior OER activities in seawater-based electrolytes compared to those in alkaline saline water containing only NaCl. To uncover the reason for such inferiority and its effect on surface reconstruction of perovskite OER pre-catalysts, a study, described herein, has been conducted on a well-known Ba0.5Sr0.5Co0.8Fe0.2O3-δ (BSCF) perovskite oxide, where an electrochemical surface reconstruction was attempted in either 0.1 M KOH or artificial seawater (pH 13). The inferior OER activity in artificial seawater has been verified, and it has been found that the surface reconstruction of BSCF in artificial seawater is only about half as effective in increasing OER activity than in 0.1 M KOH. From a screening exercise, none of the major anions (chloride, sulfate, bicarbonate and bromide ions) have a negative effect on the OER activity enhancement by surface reconstruction of BSCF. However, calcium ions, the only major divalent cation (apart from magnesium ions, which had negligible solubility as Mg(OH)2 at pH 13), was found to inhibit surface reconstruction of BSCF through CaCO3 precipitation and accumulation on the catalytic surface. Hence, it is proposed that the capability for total removal of low-solubility divalent cations such as calcium and magnesium ions from the catalytic surface is critical in encouraging the use of seawater for industrial-scale water electrolysis.